Cystic fibrosis airway epithelium remodelling: involvement of inflammation. Issue 3 (18th December 2014) - Adam, Damien; Roux‐Delrieu, Jacqueline; Luczka, Emilie; Bonnomet, Arnaud; Lesage, Julien; Mérol, Jean‐Claude; Polette, Myriam; Abély, Michel; Coraux, Christelle
Abstract Chronic inflammation is a hallmark of cystic fibrosis (CF) lung disease and airway epithelium damage and remodelling are important components of lung pathology progression in CF. Whether this remodelling is secondary to deleterious infectious and inflammatory mediators, or to alterations of CF human airway epithelial (HAE) cells, such as their hyper inflammatory phenotype or their basic cystic fibrosis transmembrane conductance regulator (CFTR) default, remains debated. In this study, we evaluated the involvement of alterations of CF HAE cells in airway epithelium remodelling. HAE cells from non‐CF and CF patients were cultured in an air–liquid interface, with and without inflammatory stimulation, along the regeneration process, and the remodelling of the reconstituted epithelium was analysed. We confirmed that CF HAE cells showed a hyperinflammatory phenotype which was lost with time. In comparison to non‐CF epithelium, CF epithelium regeneration in the absence of exogenous inflammation was higher and exhibited basal cell hyperplasia. This remodelling was mimicked by inflammatory stimulation of non‐CF cells and was absent when CF HAE cells were no longer hyperinflamed. Moreover, the number of goblet cells was similar in non‐CF and CF cultures and increased equally under inflammatory stimulation. Finally, whatever the inflammatory environment, CF cultures showed a delay in ciliated cell differentiation. In conclusion, alterations of CF HAE cells partly regulate airway epithelium remodelling following injury and regeneration. This remodelling, together with goblet cell hyperplasia induced by exogenous inflammation and alteration of ciliated cell differentiation, may worsen mucociliary clearance impairment, leading to injury. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.